If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (x + 6)(x + -3) + -52 Reorder the terms: 0 = (6 + x)(x + -3) + -52 Reorder the terms: 0 = (6 + x)(-3 + x) + -52 Multiply (6 + x) * (-3 + x) 0 = (6(-3 + x) + x(-3 + x)) + -52 0 = ((-3 * 6 + x * 6) + x(-3 + x)) + -52 0 = ((-18 + 6x) + x(-3 + x)) + -52 0 = (-18 + 6x + (-3 * x + x * x)) + -52 0 = (-18 + 6x + (-3x + x2)) + -52 Combine like terms: 6x + -3x = 3x 0 = (-18 + 3x + x2) + -52 Reorder the terms: 0 = -18 + -52 + 3x + x2 Combine like terms: -18 + -52 = -70 0 = -70 + 3x + x2 Solving 0 = -70 + 3x + x2 Solving for variable 'x'. Combine like terms: 0 + 70 = 70 70 + -3x + -1x2 = -70 + 3x + x2 + 70 + -3x + -1x2 Reorder the terms: 70 + -3x + -1x2 = -70 + 70 + 3x + -3x + x2 + -1x2 Combine like terms: -70 + 70 = 0 70 + -3x + -1x2 = 0 + 3x + -3x + x2 + -1x2 70 + -3x + -1x2 = 3x + -3x + x2 + -1x2 Combine like terms: 3x + -3x = 0 70 + -3x + -1x2 = 0 + x2 + -1x2 70 + -3x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 70 + -3x + -1x2 = 0 Factor a trinomial. (7 + -1x)(10 + x) = 0Subproblem 1
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Subproblem 2
Set the factor '(10 + x)' equal to zero and attempt to solve: Simplifying 10 + x = 0 Solving 10 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + x = 0 + -10 x = 0 + -10 Combine like terms: 0 + -10 = -10 x = -10 Simplifying x = -10Solution
x = {7, -10}
| -12v+60=48 | | 6z+7z=52 | | xy-x^2=0 | | (ab^6)(a^3b^5)= | | 3(x+2)=-2(3-2x) | | x^4-5t+4=0 | | -x^4+3t+4=0 | | x^4-10t+9=0 | | 0.4x+0.2X=x | | 4(6x+5)+6(2x+4)+4=36x+48 | | 9x-(2x-7)=28 | | 7n+2(4+6)-9=46 | | 4(3u+2)-11= | | -(u+5)+5(2u-3)= | | 4(3x+2)+3(5x+5)+6=27x+30 | | 5z+9-3z=8+z+6 | | 52-0.6(29)=33 | | -3(y+5)+2y= | | P+(p-8)+3p=112 | | -8x+9=-3x+7-5x | | 2(v+2)-5v= | | k^3-2k^2-25k+50=0 | | p-0.7(40)=22 | | 2y^2+8y-y^3=0 | | 2.4x-x= | | -a^3-5a^3+24a=0 | | 41-0.7(30)=22 | | 3x-5=75 | | -5x+(8+3x)2=2(6x+11)-27 | | 0=-h^3+36h | | (5p+7)(p^2+p-56)=0 | | 7=11y-4y |